Pengaruh Store Atmosphere dan Experiential Marketing Terhadap Minat Beli Ulang di Forty Coffee Purwakarta - Tanti Manda Sari; Ajat Sudrajat (Peneliti.net, 2022)
This study aims to determine, analyze and explain the effect of Store Atmosphere and Experiential Marketing on Repurchase Intention at Forty Coffee Purwakarta. This research uses quantitative methods with verification approaches. The sample used is 100 respondents who are consumers of Forty Coffee Purwakarta determined by the Wibisono formula and taken using nonprobability sampling technique with incidental sampling technique. The analytical technique used is path analysis. The results of this study indicate descriptively that the correlation coefficient between Store Atmosphere and Experiential Marketing is 0.883, which means that both have a very strong level of correlation. The partial effect of Experiential Marketing on Repurchase Intention has a more excellent value of 73.9% while the partial effect of Store Atmosphere on Repurchase Intention is 15.4%. The simultaneous effect value of Store Atmosphere and Experiential Marketing on Repurchase Intention is 89.3% and the remaining 10.7% was influenced by other variables not examined